Surgical aspects of international drug smuggling. Issue 6628 (9th April 1988) - Lancashire, M J R; Legg, P K; Lowe, M; Davidson, Susanna M; Ellis, B W
Abstract : The internal concealment of cocaine and other drugs in packets by "body packers"—those who swallow packets of drugs or hide them in their vagina or rectum—to avoid detection by customs officials has been increasing in both the United States and Europe. The types of package and how they are concealed are changing as the traffickers become more sophisticated in their methods. The latest parcels are less likely to burst, but obstruction of the bowel may occur. Awareness of the problem is important for staff of emergency medical services near international ports of arrival.